Towards understanding the differences between reading on paper and screen: measuring attention changes in brain activity (Libellarium: journal for research in the field of information and related sciences, 2016)
Non-intrusive experimentation and measurements can be obtained from the latest neuroscience scanning techniques and technologies. Such technologies are now quite affordable and could possibly be used for the reading process research in information and communication sciences. The research experiment focuses on measuring the changes in attention while reading the text on different media (devices). The pilot experiment showed that cheap and easy to use brainwave measuring devices can be used for testing reading processes by measuring attention (concentration). The results revealed that a reading medium (device) affects the level of attention and suggested that less attention is needed to read from paper compared to any size or type of screen. Reading books (in a foreign language) can mostly be considered neutral on the attention level scale (slightly shifted towards 53 on a 1-100 scale).
Keywords: reading; paper vs screen; attention; brain activity